Amiodarone as an autophagy promoter reduces liver injury and enhances liver regeneration and survival in mice after partial hepatectomy - Lin, Chih-Wen (Sci Rep, 2015)
The deregulation of autophagy is involved in liver regeneration. Here, we investigated the role of autophagy in the regulation of liver regeneration after partial hepatectomy (PHx) and the development of pharmacological interventions for improved liver regeneration after PHx. We show that autophagy was activated in the early stages of liver regeneration following 70% PHx in vivo. Moreover, amiodarone was associated with a significant enhancement of autophagy, liver growth, and hepatocyte proliferation, along with reduced liver injury and the termination of liver regeneration due to decreased transforming growth factor-β1 expression after 70% PHx. The promotion of autophagy appeared to selectively increase the removal of damaged mitochondria. We also found that Atg7 knockdown or pretreatment with chloroquine aggravated the liver injury associated with 70% PHx and reduced liver growth and hepatocyte proliferation. Finally, amiodarone improved liver regeneration, survival, and liver injury after 90% PHx. In conclusion, our results indicate that autophagy plays an important role in mouse liver regeneration and that modulating autophagy with amiodarone may be an effective method of improving liver regeneration, increasing survival, and ameliorating liver injury following PHx.